2001
DOI: 10.1176/appi.ajp.158.5.805
|View full text |Cite
|
Sign up to set email alerts
|

Sustained-Release Bupropion for Selective Serotonin Reuptake Inhibitor-Induced Sexual Dysfunction: A Randomized, Double-Blind, Placebo-Controlled, Parallel-Group Study

Abstract: Future studies should compare higher doses of bupropion for treating sexual dysfunction and should include a greater number of subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
3
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 13 publications
(11 reference statements)
0
51
3
2
Order By: Relevance
“…Thus, beyond the established efficacy of sildenafil for ED, specific improvement in DE could not be distinguished from improvement in erectile function. In other placebo-controlled studies in patients with SSRI-induced sexual dysfunction, Gingko biloba 46 and bupropion 47 were indistinguishable from placebo. In the one study that did show a positive sexual effect of bupropion compared to placebo, the effect was minimal and limited to libido.…”
Section: Management Of Antidepressant-associated Sexual Dysfunctionmentioning
confidence: 75%
“…Thus, beyond the established efficacy of sildenafil for ED, specific improvement in DE could not be distinguished from improvement in erectile function. In other placebo-controlled studies in patients with SSRI-induced sexual dysfunction, Gingko biloba 46 and bupropion 47 were indistinguishable from placebo. In the one study that did show a positive sexual effect of bupropion compared to placebo, the effect was minimal and limited to libido.…”
Section: Management Of Antidepressant-associated Sexual Dysfunctionmentioning
confidence: 75%
“…The antidepressant properties of bupropion have been demonstrated in controlled and open-label studies of psychiatric patient samples (22)(23)(24)(25), and it has gained favor for having efficacy comparable to that of other antidepressants yet with fewer side effects (22,26,27). Bupropion does not interfere with sexual functioning and has been associated with significantly greater weight loss compared with placebo in randomized, double-blind, placebo-controlled studies of overweight and obese individuals with (28) and without (29) depression.…”
mentioning
confidence: 99%
“…The second study was conducted by Masand et al (8), in which 30 individuals were randomly given bupropion SR 150 mg per day or placebo. The results of both studies showed that the effect of bupropion in improving sexual function was similar to placebo.…”
Section: The Effect Of Bupropion On Ssri-induced Sexual Dysfunctionmentioning
confidence: 99%
“…This disorder can affect various sexual aspects such as desire, orgasm, and arousal; however, lack of or delay in orgasm is more common than decreased sexual desire as well as arousal difficulties (7). The prevalence of this disorder is observed among 40% -45% of women and 20% -30% of men taking serotonergic antidepressants (8)(9)(10). Continuing their treatment, only 10% of patients reported spontaneous improvement in their sexual dysfunction (6).…”
Section: Introductionmentioning
confidence: 99%